Nicotine Elicits Convulsive Seizures by Activating Amygdalar Neurons - Iha, Higor A.; Kunisawa, Naofumi; Shimizu, Saki; Tokudome, Kentaro; Mukai, Takahiro; Kinboshi, Masato; Ikeda, Akio; Ito, Hidefumi; Serikawa, Tadao; Ohno, Yukihiro (Frontiers in Pharmacology, 2017)
Nicotinic acetylcholine (nACh) receptors are implicated in the pathogenesis of epileptic disorders; however, the mechanisms of nACh receptors in seizure generation remain unknown. Here, we performed behavioral and immunohistochemical studies in mice and rats to clarify the mechanisms underlying nicotine-induced seizures. Treatment of animals with nicotine (1 to 4 mg/kg, i.p.) produced motor excitement in a dose-dependent manner and elicited convulsive seizures at 3 and 4 mg/kg. The nicotine-induced seizures were abolished by a subtype non-selective nACh antagonist, mecamylamine (MEC). A α7 nACh antagonist, methyllycaconitine (MLA), also significantly inhibited nicotine-induced seizures whereas a α4β2 nACh antagonist, dihydro-β-erythroidine (DHβE), affected only weakly. Topographical analysis of Fos protein expression, a biological marker of neural excitation, revealed that a convulsive dose (4 mg/kg) of nicotine region-specifically activated neurons in the piriform cortex, amygdala, medial habenula, paratenial thalamus, anterior hypothalamus and solitary nucleus among 48 brain regions examined, and this was also suppressed by MEC. In addition, electric lesioning of the amygdala, but not the piriform cortex, medial habenula and thalamus, specifically inhibited nicotine-induced seizures. Furthermore, microinjection of nicotine (100 and 300 μg/side) into the amygdala elicited convulsive seizures in a dose-related manner. The present results suggest that nicotine elicits convulsive seizures by activating amygdalar neurons mainly via α7 nACh receptors.